Community Service Empowerment of Agricultural Products - Widyasmoro Widyasmoro; Zuhud Rozaki (Peneliti Teknologi Teknik Indonesia, 2021)
Dusun Dlingseng is located in Banjaroyo Village, Kalibawang District, Kulon Progo Regency, which is the location of regular and international KKN in February and March 2019, where the majority of villagers rely on their main livelihood as farmers and ranchers. In addition to these two sources of livelihood, Dusun Dlingseng is also where the Banjaroyo Embung operates or often known as a mini reservoir. Where apart from being a place of recreation, this Embung and its surroundings are a place for the Dlingseng community to sell their garden produce. Agricultural products produced in Dlingseng Hamlet such as cassava, coffee, corn, cassava, coffee, rambutan, coconut, durian and others are grown on the farmers' respective lands. Usually they process cassava into